(untitled) (Journal of Health, Population and Nutrition, 2013)
To assess the validity of a questionnaire developed for parents of preschool children to know their physical activity (PA) status, we compared the questionnaire results with the measures of accelerometer for childrens activities. Thirty-five preschoolers who wore the accelerometer for at least 10 hours daily on 3 weekdays and one weekend day were included in the analyses. Time spent in activities of varied intensity was calculated by applying 15-second ActiGraph count cutoffs (ACC). Parents perceptions of their childrens PA were associated with the percentage of vigorous and moderate physical activity recorded with ACC at r=0.62 (p=0.0001). An association was shown between the percentage of a childs time spent in vigorous physical activity, as reported by parents, with that measured by ACC at r=0.53 (p=0.001). Results of this study suggest that the designed questionnaire might be a useful tool for assessing childrens activity while, additionally, it warrants further investigation on larger samples of children DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13327 J HEALTH POPUL NUTR 2012 Dec;30(4):439-446